Voltage Stability Analysis and Stability Improvement of Power System - Pavithren Pavithren; Raman Raghu Raman; Pratap Nair; K. Nithiyananthan (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The main objective of this research work is to analysis the voltage stability of the power system network and its improvement in the network.voltage stability of a power system. A system enters a state of voltage instability when a disturbance, increase in load demand, or change in system condition causes a progressive and an uncontrollable drop in voltage or voltage collapse. The continuing increase in demand for electric power has resulted in an increasingly complex, interconnected system, forced to operate closer to the limits of the stability. This has necessitated the implementation of techniques for analyzing and detecting voltage collapse in bus bar or lines prior to its occurrence. Simple Newton Raphson algorithm based voltage stability analysis has been carried out. Matlab based simulations for all the factors that causes voltage instability has been implemented and analyzed for an IEEE 30 bus system. The proposed model is able to identify the behavior of the power systems, network under various voltage stability conditions and its possibility of recovery/stability improvement of the power system network has been discussed.